Implementasi Pembelajaran Tematik pada Masa Pandemi Covid-19 di Kelas II MI As-Salam O’o Dompu - Akhmad Asyari; diah cahyani (Universitas Islam Negeri (UIN) Mataram, 2021)
This study aims to explore in depth about the implementation, challenges and efforts of teachers to overcome various problems in thematic learning in Islamic primary school. This research uses descriptive research where sampling is done by purposive and snowball. The data collection techniques using interviews, observation and documentation. The results of the study describe that the implementation of thematic learning is guided by the lesson plans and refers to the theme as normal conditions. The problems faced in the application of thematic learning are factored in by factors of readiness and teacher understanding of planning, implementation, and evaluation. The teacher's efforts to overcome the various problems above are through regular discussions about thematic learning of the 2013 curriculum as well as exploring and understanding in detail about the important components in planning, implementing and evaluating as well as effectively utilizing the surrounding environment as a learning resource.